The Influence of Job Satisfaction and Motivation on Work Commitment among Two Star Hotel Employees in Bukittinggi with Compensation as a Mediating Variable - Nathaliena, MV. Sheryl (UPI YPTK Journal of Business and Economics, 2022)
This study aims to examine the effect of satisfaction and work motivation on work commitment of two-star hotel employees in Bukittinggi with compensation as the intervening variable. The sample selection technique used purposive sampling and a total of 137 samples were obtained. The data analysis technique uses Structural Equition Modeling (SEM) with Partial Least Square (PLS). Based on the results of the analysis it is known that job satisfaction has no significant effect on employee compensation at two-star hotels in Bukittinggi City. Work motivation has a significant effect on employee compensation at two-star hotels in the City of Bukittinggi. Job satisfaction has a significant effect on employee commitment to a two-star hotel in the city of Bukittinggi. Work motivation has a significant effect on employee commitment to a two-star hotel in the city of Bukittinggi. Compensation has no significant effect on employee work commitment at a two-star hotel in Bukittinggi. Job satisfaction has no significant effect on work commitment through employee compensation at two-star hotels in the city of Bukittinggi. Work motivation has no significant effect on work commitment through employee compensation at a two-star hotel in the city of Bukittinggi.